2016
DOI: 10.1371/journal.pone.0150842
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Mediated Chemokine Responses in Human Airway Smooth Muscle Cells

Abstract: Airway smooth muscle (ASM) cells play a critical role in the pathophysiology of asthma due to their hypercontractility and their ability to proliferate and secrete inflammatory mediators. microRNAs (miRNAs) are gene regulators that control many signaling pathways and thus serve as potential therapeutic alternatives for many diseases. We have previously shown that miR-708 and miR-140-3p regulate the MAPK and PI3K signaling pathways in human ASM (HASM) cells following TNF-α exposure. In this study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…miR-708 inhibited mRNA expression as well as release of CXCL8 along with other chemokines and asthma related genes in human airway smooth muscle cells. Another miRNA, miR-140-3p, also inhibited CXCL8 mRNA expression, but not the CXCL8 release 479. There are several miRNAs that are aberrantly expressed in our body, indirectly regulating CXCL8 release.…”
Section: Antibody Therapymentioning
confidence: 98%
“…miR-708 inhibited mRNA expression as well as release of CXCL8 along with other chemokines and asthma related genes in human airway smooth muscle cells. Another miRNA, miR-140-3p, also inhibited CXCL8 mRNA expression, but not the CXCL8 release 479. There are several miRNAs that are aberrantly expressed in our body, indirectly regulating CXCL8 release.…”
Section: Antibody Therapymentioning
confidence: 98%
“…Interestingly, PGC1α activates the PINK1/Parkin mitophagy pathway, which is involved in ubiquitination of Mfn2 (Chen and Dorn, 2013;Basso et al, 2018;McLelland et al, 2018). Similarly, a growing list of miRNA has been implicated in the downregulation of Mfn2 but it is not clear if they are expressed in hASM and whether XBP1 is involved in their regulation (Kuhn et al, 2010;Dileepan et al, 2016;Purohit et al, 2019). Previous studies have also shown that XBP1 induces several miRNA but their potential effect on Mfn2 has not been explored and again it's not known if these miRNA are expressed in hASM (Kuhn et al, 2010;Dileepan et al, 2016;Purohit et al, 2019).…”
Section: Mfn2 and Er Stress Responsementioning
confidence: 99%
“…Similarly, a growing list of miRNA has been implicated in the downregulation of Mfn2 but it is not clear if they are expressed in hASM and whether XBP1 is involved in their regulation (Kuhn et al, 2010;Dileepan et al, 2016;Purohit et al, 2019). Previous studies have also shown that XBP1 induces several miRNA but their potential effect on Mfn2 has not been explored and again it's not known if these miRNA are expressed in hASM (Kuhn et al, 2010;Dileepan et al, 2016;Purohit et al, 2019). The PERK and ATF6 pathway have also been suggested to affect Mfn2 expression, either through PGC1α, mitophagy or ERAD pathways (Morris et al, 2018).…”
Section: Mfn2 and Er Stress Responsementioning
confidence: 99%
“…Furthermore, miR-708 transfection also resulted in inhibition of expression of genes known to contribute to the pathogenesis of asthma such as RARRES2, CD44 and ADAM33 . These results showed that there are genes targeted by both miRNAs, while exerting distinct effects on inflammation-associated gene expression in human ASM cells (Dileepan, et al, 2016). Many of the chemokines whose expression is modulated by the miRNAs are involved in the recruitment of inflammatory cells into the airways such as eosinophils, basophils, mast cells and T lymphocytes in allergic airway disease.…”
Section: Regulation Of Cd38 Expression In Human Airway Smooth Musclementioning
confidence: 92%
“…We propose that targeted delivery of these miRNAs into the lungs should result in significant anti-inflammatory effects. In this context, in our recent studies we examined the effect of transfection of human ASM cells with miR-140-3p and miR-708 on candidate inflammation-associated gene expression and validated the expression of some of these genes using qRT-PCR and release of some of the chemokines by ELISA (Dileepan, et al, 2016). Among the most significant biologic functions for the differentially expressed gene set following miRNA transfection in cells exposed to TNF-α were decreased inflammatory response, cytokine expression and signaling.…”
Section: Regulation Of Cd38 Expression In Human Airway Smooth Musclementioning
confidence: 99%